Correction: The aromaticity of dicupra[10]annulenes. Issue 17 (12th April 2017) - Grande-Aztatzi, Rafael; Mercero, Jose M.; Matito, Eduard; Frenking, Gernot; Ugalde, Jesus M.
Abstract : Correction for 'The aromaticity of dicupra[10]annulenes' by Rafael Grande-Aztatzi et al., Phys. Chem. Chem. Phys., 2017, 19, 9669–9675.